Psychogenic nonepileptic seizures: clinical characteristics and outcome - Volbers, Bastian; Walther, Katrin; Kurzbuch, Katrin; Erdmann, Laura; Gollwitzer, Stephanie; Lang, Johannes; Onugoren, Muejgan Dogan; Schwarz, Michael; Schwab, Stefan; Hamer, Hajo (Brain and Behavior, 2022)
Background: Clinical characteristics, outpatient situation, and outcome in patients with psychogenic nonepileptic seizures (PNES) remain to be elucidated. Methods: Patients diagnosed with PNES after video-electroencephalography (EEG) monitoring (VEM) 03/2000–01/2016 at the Erlangen Epilepsy Center were surveyed between June 2016 and February 2017. Primary outcome was PNES cessation defined as no PNES episodes within > = 12 months prior to the interview. Secondary outcome variables included quality of life (QoL) and dependency. Sensitivity analysis included patients with proven PNES during VEM without comorbid epilepsy. Results: Ninety-nine patients were included (median age 38 (interquartile range (IQR 29–52)) years; 68 (69%) females, follow-up 4 (IQR 2.1–7.7) years). Twenty-eight (28%) patients suffered from comorbid epilepsy. Twenty-five (25%) patients reported PNES cessation. Older age at symptom onset (odds ratio (OR) related to PNES cessation: 0.95 (95% CI 0.90–0.99)), comorbid epilepsy (OR 0.16 (95% CI 0.03–0.83)), anxiety disorder (OR 0.15 (95% CI 0.04–0.61)), and tongue biting (OR 0.22 (95% CI 0.03–0.91)) remained independently associated with ongoing PNES activity after adjustment. Sensitivity analysis (n = 63) revealed depressive disorder (OR 0.03 (95% CI 0.003–0.34)) instead of anxiety as independent predictor, while this seemed relevant only in patients older than 26 years at onset (OR 0.04 (95% CI 0.002–0.78) versus OR 0.21 (95% CI 0.02–1.84) in patients younger than 26 years). PNES cessation was associated with increased median QoL (8 (IQR 7–9) versus 5.5 (IQR 4–7); p <.001) and an increased frequency of financial independency (14 (56%) versus 21 (28%); p =.01). Conclusions: We found poor outcomes in PNES especially in older patients at onset with comorbid depressive disorder. Comorbid epilepsy also seems to be a major risk factor of ongoing PNES activity, which in turn affects patients’ daily living.
CRIS-Team Scopus Importer:2022-04-22
Keywords: activities of daily living; mental disorders; nonepileptic seizures; patient-relevant outcome; prognosis

Psychosocial long-term outcome in patients with psychogenic non-epileptic seizures - Walther, Katrin; Volbers, Bastian; Erdmann, Laura; Kurzbuch, Katrin; Lang, Johannes; Müller, Tamara; Reindl, Caroline; Schwarz, Michael; Schwab, Stefan; Hamer, Hajo (Seizure-European Journal of Epilepsy, 2020)
Purpose: To evaluate psychosocial long-term outcome in patients diagnosed with psychogenic nonepileptic seizures (PNES) and to predict outcome of PNES, economic status, and quality of life (QoL) at follow-up. Methods: Patients diagnosed with PNES in the video-EEG-monitoring unit at our Epilepsy center between 2002–2016 were contacted by phone 1–16 years after communicating the diagnosis. Patients underwent a structured interview asking for current PNES status, psychosocial situation (economic status, marital status, setting of living, driving), depression, and QoL. Results: Of 70 PNES patients without comorbid epilepsy (age: 41.1 ± 13.5 years; 74 % female, follow-up: 5.2 ± 4.2 years), 23 patients (33 %) reported to be free of PNES during the last 12 months. Patients with cessation of PNES were younger at PNES onset (p < .01) and diagnosis (p < .01) and had a higher education (p < .05). At follow-up, the proportion of economically active patients only increased in individuals with cessation of PNES (p < .001) while an increased number of patients with persisting PNES relied on governmental support (p < .001). Cessation of PNES was associated with better mood (p < .01) and QoL (p < .001). In multiple regression models, cessation of PNES was only predicted by younger age at onset, while good economic outcome was determined by younger age and good economic status at diagnosis and cessation of PNES at follow-up. Good QoL at follow-up was predicted by low depressive symptoms, freedom of PNES, and economic activity at follow-up. Conclusion: Long-term outcome in patients with PNES remains to be poor and the majority of patients continue to have PNES. Cessation of PNES was associated with good economic outcome, mood, and QoL.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Employment; Long-term outcome; Marital status; Mood; Psychogenic non-epileptic seizures; Quality of life